How Asia works success and failure in the world's most dynamic region - Studwell, Joe (Tantor Media, 2017)
In the 1980s and 1990s many in the West came to believe in the myth of an East-Asian economic miracle, with countries seen as not just development prodigies but as a unified bloc, culturally and economically similar, and inexorably on the rise. In How Asia Works, Joe Studwell distills extensive research into the economics of nine countries-Japan, South Korea, Taiwan, Indonesia, Malaysia, Thailand, the Philippines, Vietnam, and China-into an accessible narrative that debunks Western misconceptions, shows what really happened in Asia and why, and for once makes clear why some countries have boomed while others have languished. Impressive in scope, How Asia Works is essential listening for anyone interested in a region that will shape the future of the world.
Downloadable audio file
Keywords: Economic development -- East Asia; 2000-2099; BUSINESS & ECONOMICS; General; Economic development; Economic history; Extrême-Orient; Conditions économiques; 21e siècle; East Asia; Downloadable audio books; Audiobooks; Livres audio; East Asia -- Economic conditions -- 21st century